Individual utilisation thresholds and exploring how GPs’ knowledge of their patients affects diagnosis: a qualitative study in primary care - Michiels-Corsten, Matthias (Br J Gen Pract, 2017)
BACKGROUND: One of the tenets of general practice is that continuity of care has a beneficial effect on patient care. However, little is known about how continuity can have an impact on the diagnostic reasoning of GPs. AIM: To explore GPs’ diagnostic strategies by examining GPs’ reflections on their patients’ individual thresholds for seeking medical attention, how they arrive at their estimations, and which conclusions they draw. DESIGN AND SETTING: Qualitative study with 12 GPs in urban and rural practices in Germany. METHOD: After each patient consultation GPs were asked to reflect on their diagnostic reasoning for that particular case. Qualitative and quantitative analyses of consultations and interview content were undertaken. RESULTS: A total of 295 primary care consultations were recorded, 134 of which contained at least one diagnostic episode. When elaborating on known patients, GPs frequently commented on how ‘early’ or ‘late’ in an illness progression a patient tended to consult. The probability of serious disease was accordingly regarded as high or low. This influenced GPs’ behaviour regarding further investigations or referrals, as well as reassurance and watchful waiting. GPs’ explanations for a patient’s utilisation threshold comprised medical history, the patient’s characteristics, family background, the media, and external circumstances. CONCLUSION: The concept of an individual threshold for the utilisation of primary care would explain how GPs use their knowledge of individual patients and their previous help-seeking behaviour for their diagnostic decision making. Whether the assumption behind this concept is valid, and whether its use improves diagnostic accuracy, remains to be investigated.